2013
DOI: 10.1038/mtna.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Versus Nasal Transduction of Murine Airways With GP64-pseudotyped Viral Vectors

Abstract: Persistent viral vector-mediated transgene expression in the airways requires delivery to cells with progenitor capacity and avoidance of immune responses. Previously, we observed that GP64-pseudotyped feline immunodeficiency virus (FIV)-mediated gene transfer was more efficient in the nasal airways than the large airways of the murine lung. We hypothesized that in vivo gene transfer was limited by immunological and physiological barriers in the murine intrapulmonary airways. Here, we systematically investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…In a previous study, we observed that GP64-FIV transduced mouse nasal airways with greater efficiency than the intrapulmonary airways. 10 This observation was true both in vivo and in welldifferentiated primary cultures derived from mouse nasal septa or trachea. We hypothesized that the differential expression pattern was due to a cellspecific factor.…”
Section: Expression Of Lentiviral Restriction Factors In Mouse Airwaysmentioning
confidence: 82%
See 3 more Smart Citations
“…In a previous study, we observed that GP64-FIV transduced mouse nasal airways with greater efficiency than the intrapulmonary airways. 10 This observation was true both in vivo and in welldifferentiated primary cultures derived from mouse nasal septa or trachea. We hypothesized that the differential expression pattern was due to a cellspecific factor.…”
Section: Expression Of Lentiviral Restriction Factors In Mouse Airwaysmentioning
confidence: 82%
“…We previously demonstrated that FIV pseudotyped with the envelope glycoprotein from baculovirus Autographa californica multinucleocapsid nucleopolyhedrosis virus (GP64) confers apical entry into well-differentiated primary cultures of human, mouse, and pig airway epithelial cells. 4,[8][9][10] We further demonstrated that GP64-FIV efficiently transduced the airways of mice or pigs in vivo, was repeatedly administered without the generation of blocking immune responses, and expressed a reporter gene for the life span of mice. 9,11 Thus, GP64-FIV is a candidate gene therapy reagent for genetic pulmonary diseases such as cystic fibrosis.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Lentiviral vectors transduce both dividing and nondividing cells, integrate into the host genome, and provide long-term trans-gene expression (10, 11). A feline immunodeficiency virus–based (FIV-based) viral vector pseudotyped with the baculovirus envelope protein GP64 transduces epithelial cells at the apical surface and persistently expresses a transgene of interest in mouse airways (12, 13). We previously demonstrated that FIV pseudotyped with the GP64 envelope from baculovirus efficiently transduces both human and pig airway epithelia (12, 14).…”
Section: Introductionmentioning
confidence: 99%